Integrating planetary health education into tertiary curricula: a practical toolbox for implementation - Lokmic-Tomkins, Zerina; Barbour, Liza; LeClair, Jessica; Luebke, Jeneile; McGuinness, Sarah L.; Limaye, Vijay S.; Pillai, Parvathy; Flynn, Maxfield; Kamp, Michael A.; Leder, Karin; Patz, Jonathan A. (Frontiers in Medicine, 2024)
Objective: To present a series of case studies from our respective countries and disciplines on approaches to implementing the Planetary Health Education Framework in university health professional education programs, and to propose a curriculum implementation and evaluation toolbox for educators to facilitate the adoption of similar initiatives in their programs. We emphasize the importance of applying an Indigenous lens to curriculum needs assessment, development, implementation, and evaluation.Methods: Case studies from Australia and United States were collated using a six-stage design-based educational research framework (Focus, Formulation, Contextualization, Definition, Implementation, Evaluation) for teaching planetary health and methods of curriculum evaluation. These components were then mapped to derive the curriculum implementation toolbox reflecting the six-stage designbased educational research framework.The case studies demonstrated different approaches to successful integration of the Planetary Health Education Framework in medicine, nursing, public health, and allied health disciplines. This integration often involved Indigenous perspectives on environmental stewardship, holistic health, and community well-being into the curriculum. The case studies also highlighted the importance of community engagement, cultural competency, and interdisciplinary collaboration in curriculum development. Findings from case studies were used to propose a curriculum implementation toolbox to assist educators in adapting and integrating planetary health education into their own programs. Discussion: While valuable frameworks for teaching planetary health in health science programs exist, challenges remain in implementing these frameworks in real-world educational environments. The proposed curriculum implementation toolbox offers practical strategies and resources for educators to incorporate these principles into their teaching. Additionally, the case studies reported here contribute to the growing body of literature on planetary health education pertinent to addressing the triple planetary crisis.